From health tips to tech hacks, find it all on IDNLearn.com. Discover comprehensive answers to your questions from our community of experienced professionals.
Sagot :
Alright, let's tackle this problem step-by-step.
Given:
[tex]\[ \cos \left(\theta + 30^\circ\right) = \frac{1}{2} \sin \theta \][/tex]
We will use the angle addition formula for the cosine function:
[tex]\[ \cos \left(\theta + 30^\circ\right) = \cos \theta \cos 30^\circ - \sin \theta \sin 30^\circ \][/tex]
We know from trigonometric identities that:
[tex]\[ \cos 30^\circ = \frac{\sqrt{3}}{2} \quad \text{and} \quad \sin 30^\circ = \frac{1}{2} \][/tex]
Substituting these values into the angle addition formula, we get:
[tex]\[ \cos \left(\theta + 30^\circ\right) = \cos \theta \cdot \frac{\sqrt{3}}{2} - \sin \theta \cdot \frac{1}{2} \][/tex]
Let's substitute this back into the given equation:
[tex]\[ \cos \theta \cdot \frac{\sqrt{3}}{2} - \sin \theta \cdot \frac{1}{2} = \frac{1}{2} \sin \theta \][/tex]
Now, we need to simplify this equation:
[tex]\[ \cos \theta \cdot \frac{\sqrt{3}}{2} - \sin \theta \cdot \frac{1}{2} - \frac{1}{2} \sin \theta = 0 \][/tex]
Combine the [tex]\(\sin \theta\)[/tex] terms:
[tex]\[ \cos \theta \cdot \frac{\sqrt{3}}{2} - \sin \theta \left(\frac{1}{2} + \frac{1}{2}\right) = 0 \][/tex]
This simplifies to:
[tex]\[ \cos \theta \cdot \frac{\sqrt{3}}{2} - \sin \theta \cdot 1 = 0 \][/tex]
or:
[tex]\[ \cos \theta \cdot \frac{\sqrt{3}}{2} = \sin \theta \][/tex]
Rearranging the terms gives:
[tex]\[ \cos \theta \cdot \frac{\sqrt{3}}{2} = \sin \theta \][/tex]
To isolate [tex]\(\tan \theta\)[/tex], divide both sides by [tex]\(\cos \theta\)[/tex]:
[tex]\[ \frac{\sqrt{3}}{2} = \frac{\sin \theta}{\cos \theta} \][/tex]
Recall that [tex]\(\frac{\sin \theta}{\cos \theta} = \tan \theta\)[/tex]:
So, we have:
[tex]\[ \tan \theta = \frac{\sqrt{3}}{2} \][/tex]
Hence, we have shown that:
[tex]\[ \tan \theta = \frac{\sqrt{3}}{2} \][/tex]
This completes the solution.
Given:
[tex]\[ \cos \left(\theta + 30^\circ\right) = \frac{1}{2} \sin \theta \][/tex]
We will use the angle addition formula for the cosine function:
[tex]\[ \cos \left(\theta + 30^\circ\right) = \cos \theta \cos 30^\circ - \sin \theta \sin 30^\circ \][/tex]
We know from trigonometric identities that:
[tex]\[ \cos 30^\circ = \frac{\sqrt{3}}{2} \quad \text{and} \quad \sin 30^\circ = \frac{1}{2} \][/tex]
Substituting these values into the angle addition formula, we get:
[tex]\[ \cos \left(\theta + 30^\circ\right) = \cos \theta \cdot \frac{\sqrt{3}}{2} - \sin \theta \cdot \frac{1}{2} \][/tex]
Let's substitute this back into the given equation:
[tex]\[ \cos \theta \cdot \frac{\sqrt{3}}{2} - \sin \theta \cdot \frac{1}{2} = \frac{1}{2} \sin \theta \][/tex]
Now, we need to simplify this equation:
[tex]\[ \cos \theta \cdot \frac{\sqrt{3}}{2} - \sin \theta \cdot \frac{1}{2} - \frac{1}{2} \sin \theta = 0 \][/tex]
Combine the [tex]\(\sin \theta\)[/tex] terms:
[tex]\[ \cos \theta \cdot \frac{\sqrt{3}}{2} - \sin \theta \left(\frac{1}{2} + \frac{1}{2}\right) = 0 \][/tex]
This simplifies to:
[tex]\[ \cos \theta \cdot \frac{\sqrt{3}}{2} - \sin \theta \cdot 1 = 0 \][/tex]
or:
[tex]\[ \cos \theta \cdot \frac{\sqrt{3}}{2} = \sin \theta \][/tex]
Rearranging the terms gives:
[tex]\[ \cos \theta \cdot \frac{\sqrt{3}}{2} = \sin \theta \][/tex]
To isolate [tex]\(\tan \theta\)[/tex], divide both sides by [tex]\(\cos \theta\)[/tex]:
[tex]\[ \frac{\sqrt{3}}{2} = \frac{\sin \theta}{\cos \theta} \][/tex]
Recall that [tex]\(\frac{\sin \theta}{\cos \theta} = \tan \theta\)[/tex]:
So, we have:
[tex]\[ \tan \theta = \frac{\sqrt{3}}{2} \][/tex]
Hence, we have shown that:
[tex]\[ \tan \theta = \frac{\sqrt{3}}{2} \][/tex]
This completes the solution.
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Discover insightful answers at IDNLearn.com. We appreciate your visit and look forward to assisting you again.